Equity and opportunity to learn in basic education - Cervini, Rubén (Profesorado, Revista de Currículum y Formación del Profesorado, 2011)
This study investigated the relationship between the ’opportunity to learn ’(OTL) offered by the teacher to students in the classroom and their mathematics achievement. Data from the 2000 - 6th grade Primary School Census from the Minister of Education of Argentina are analyzed using multilevel linear modeling with two levels (student and classroom) was used to analyze OTL effects on achievement. Student math score was based on a standard test applied to the students at the end of the academic year. Seven different indicators from a teacher questionnaire were used to measure OTL concept. School climate and institutional organization are included in the analysis. It was found that OTL is a significant predictor of mathematics test score even after students socioeconomic background, socioeconomic school context and level of educational resources in school were controlled. Furthermore, the data analysis shows that OTL is an important intermediate variable between socioeconomic school context and achievement and it is a multidimensional concept, suggesting that different indicators should be used in order to properly estimate the effect of OTL on achievement.